Fabrication of nanocones by RIE on GaP. (September 2019) - Eliáš, P; Haščík, Š
Abstract: GaP(111)B substrate was etched through colloidal self-assembled randomly distributed 30nn Au nanoparticles by RIE. We looked into how GaP nanocones (NCs) formed with respect to the chamber pressure and etching duration, and the use of electron cyclotron resonance (ECR) RIE mode. The NCs were steep-walled in RIE, and those produced by ECR RIE were bell shaped. The NC length increased with etching duration for the same chamber pressure. The NCs were shorter and slightly steeper with decreased pressure for the same etching duration. The NCs that had the Au particles eradicated during the etching process became blunt and were gradually diminished.